Analisis Pemahaman Mahasiswa Fisika Universitas Negeri Gorontalo Tentang Sinar-X - Manisa, Aziza; Asiah, Nur; Sari, Widya Priskila; Nuranisya, Dwita; Kurniasari, Septiana (UNIVERSITAS INDRAPRASTA PGRI, 2025)
The use of X-rays in the health/medical field is used to diagnose of patient diseases, and for therapy. However, X-rays not only provide health benefits, but can also cause adverse effects for radiation officers, patients, and the general public. This research aims to analyze the understanding of Physics students at Universitas Negeri Gorontalo about X-rays. This research method uses descriptive research with a quantitative approach. The research instrument used was an understanding test sheet distributed to 24 respondents. Based on the results of the data analysis, overall it is known that the understanding of Physics students at Universitas Negeri Gorontalo about X-rays is 75.8%, or is in the Very Good criteria. This shows that most students are able to understand X-rays.